(untitled) (Stavební obzor - Civil Engineering Journal, 2021)
An industrial-scale production and experimental investigation was conducted in order to evaluate the constructability and structural performance of different concrete pipes incorporating discrete synthetic fibers. The results indicated that synthetic fibers enable design of plain concrete pipes with a desired balance of strength and ductility. Analytical models were developed for predicting the load-carrying capacity of concrete pipes without steel reinforcement that are reinforced with discrete fibers.